2019
DOI: 10.1590/0034-7167-2018-0561
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Nursing in best practices of labor and delivery care

Abstract: Objective: to evaluate the association of Obstetric Nursing in the best practices of delivery and birth care in maternity hospitals. Method: a cross-sectional study, with 666 women selected for delivery. Parturition obstetric practices performed by professionals were categorized into: clearly useful practices that should be encouraged, practices that are clearly harmful or ineffective and that should be eliminated and practices used inappropriately at the time of parturition. Results: clearly useful practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 25 publications
2
15
0
24
Order By: Relevance
“…There are also possible long-term complications, such as dyspareunia, anorectal dysfunction, and sexual dysfunction (2,10) . It is noteworthy that the use of good practices during labor, recommended by WHO, can reduce the likelihood of unnecessary interventions and have positive effects on the delivery experience of these women (14,16) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also possible long-term complications, such as dyspareunia, anorectal dysfunction, and sexual dysfunction (2,10) . It is noteworthy that the use of good practices during labor, recommended by WHO, can reduce the likelihood of unnecessary interventions and have positive effects on the delivery experience of these women (14,16) .…”
Section: Resultsmentioning
confidence: 99%
“…They aim to guide the professional's conduct. They are classified as: clearly useful practices that should be encouraged, clearly harmful or ineffective practices that must be eliminated, and practices used inappropriately at the time of labor and delivery; this category includes the episiotomy (1,(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the support found in information about childbirth physiology in different relationships established is essential for women to believe in their ability to give birth, and also, when experienced during pregnancy, to promote and strengthen their autonomy (30) . In a randomized clinical trial, the intervention during pregnancy about the evolution of stages of labor, interventions and their indications helped to experience this moment with less fear (31) .…”
Section: They Want a Peaceful Delivery With Less Pain Fast And Without Interventionsmentioning
confidence: 99%
“…The presence of qualified professionals to encourage good practices was observed to be beneficial for qualification of obstetric care. A cross-sectional observational study identified an increase in good practices in assisting the parturition process in institutions where nurse-midwives were present (30) .…”
Section: They Want a Peaceful Delivery With Less Pain Fast And Without Interventionsmentioning
confidence: 99%
“…Estudos têm apontado que há uma maior adesão das enfermeiras obstétricas em orientar sobre as diferentes posições que podem ser adotadas no trabalho de parto, possibilitando sua livre escolha. Estas profissionais, ao se apropriarem de práticas baseadas em evidências, potencializam a voz da mulher no processo de parto e nascimento 19,20 .…”
Section: ] (M5)unclassified